A Spatio-Temporal Changes in Cropping Pattern and Cropping Intensity in Agriculture to Get a Business Profit in Jammu and Kashmir - Javaid Ahmad Andrabi (Budapest International Research and Critics University, 2018)
In the present paper an attempt has been made to analyze spatio-temporal changes in cropping pattern and cropping intensity in agriculture of Jammu and Kashmir. Data were obtained from Statistical Abstract of Jammu and Kashmir. Copping pattern and cropping intensity have been presented in the percentage forms. Results of the study reveal that cropping pattern is much diverse with high level of cropping intensity in agriculture of the state. It has been found that maize is still most cultivated crop in the state, covering an area of 27.4 % to total cropped area during 2010-11. Wheat has been found second most cultivated crop with increasing trend of area. The area under rice and pulses crop has decreased rapidly over the period. Cropping intensity has also continuously increased from 119.70% in 1965-66 to 155.79 % in 2010-11. The highest cropping intensity has been recorded in samba (212.63%) whereas lowest registered in Kupwara (100%) district of the state.